2008
DOI: 10.1002/anie.200800233
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Synthesis of a Pochonin Library Targeting HSP90 and In Vivo Efficacy of an Identified Inhibitor

Abstract: Make a clean breast of it: The generation of a library of pochonin D derivatives by a solid-phase approach has led to the discovery of pochoxime (see scheme), a potent inhibitor of the heat-shock protein 90, with over 100-fold improved incellular activity. Pochoxime was found to be effective in breast tumor xenografts, leading to a reduction in the tumor size

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…In this study, we evaluated NXD30001, a novel HSP90 inhibitor based on the radicicol backbone, from NexGenix Pharmaceuticals (New York, NY, USA; Barluenga et al 2008Barluenga et al , 2009Wang et al 2009;Zhu et al 2010). We report that NXD30001 had a neuroprotective profile similar to geldanamycin in the ALS1 culture model, but with less toxicity.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we evaluated NXD30001, a novel HSP90 inhibitor based on the radicicol backbone, from NexGenix Pharmaceuticals (New York, NY, USA; Barluenga et al 2008Barluenga et al , 2009Wang et al 2009;Zhu et al 2010). We report that NXD30001 had a neuroprotective profile similar to geldanamycin in the ALS1 culture model, but with less toxicity.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In plasma, NXD30001 cleared quickly and reached near the lower limit of quantitation level at 6 h. In contrast, NXD30001 levels in brain, spinal cord, liver, and muscle were still above the neuroprotective concentration used in culture (40 nM, equivalent to 20 ng/g of tissue) at 6 h, despite substantial decrease from levels at 1 h. Drug levels in liver and muscle were much higher than those in nervous tissues. To convert ng/g to molar concentration, multiply by 0.5 turnover of cell signaling molecules that are HSP90 client proteins (Barluenga et al 2008Wang et al 2009;Zhu et al 2010;Tanaka et al 2013).…”
Section: G93amentioning
confidence: 99%
“…Subsequent conditional deletion of Hsp90α, in adult mice, showed that the chaperone is essential for germ cell development in mature adult testes. 34 Extended exposure of pubertal male mice to high doses of the Hsp90α/β N-terminal domain inhibitor, pochoxime A, a new radicicol derivative with efficacy favorable for entry into brain and testes, 28,165,166 caused testicular atrophy in some of the animals similar to the phenotype seen in mice with genetic disruption of Hsp90α. 33 These results suggest that such drugs could be used to generate pharmacological infertility in male mice.…”
Section: Male Contraceptionmentioning
confidence: 99%
“…The NPs pochonin D (6) and radicicol (7) were used as library template (8) by Winssinger's group (Fig. 7.13) [195]. This template was chosen to study the effect of structural modifications of pochonin on its activity on the heat-shock protein 90 (HSP90).…”
Section: Natural Products As Source Of Inspirationmentioning
confidence: 99%